2016
DOI: 10.3390/rs8100787
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of LiDAR and APEX Hyperspectral Data for High-Resolution Urban Land Cover Mapping

Abstract: Land cover mapping of the urban environment by means of remote sensing remains a distinct challenge due to the strong spectral heterogeneity and geometric complexity of urban scenes. Airborne imaging spectroscopy and laser altimetry have each made remarkable contributions to urban mapping but synergistic use of these relatively recent data sources in an urban context is still largely underexplored. In this study a synergistic workflow is presented to cope with the strong diversity of materials in urban areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…In general, the accuracy values of our spectral unmixing results, obtained using a combination of AMUSES and MESMA, are in line with typical values found by other studies in the urban environment, using a variety of different image data, library pruning approaches and spectral unmixing techniques [16,47,[55][56][57]. In particular, overall RMSE values from our first experiment on the Berlin data closely match the performance reported by a study conducted on the same data using machine learning-based approaches [48].…”
Section: Urban Land Cover Mapping Using Hyperspectral Imagerysupporting
confidence: 71%
See 2 more Smart Citations
“…In general, the accuracy values of our spectral unmixing results, obtained using a combination of AMUSES and MESMA, are in line with typical values found by other studies in the urban environment, using a variety of different image data, library pruning approaches and spectral unmixing techniques [16,47,[55][56][57]. In particular, overall RMSE values from our first experiment on the Berlin data closely match the performance reported by a study conducted on the same data using machine learning-based approaches [48].…”
Section: Urban Land Cover Mapping Using Hyperspectral Imagerysupporting
confidence: 71%
“…However, significant mapping errors were still observed, particularly the overestimation of roof and underestimation of pavement and soil (Figure 8). The same problems are observed by other urban mapping studies (e.g., [16,48]) and are caused by the well-known phenomenon of spectral confusion between soil, pavement and roof materials, which are typically made of the same materials (e.g., asphalt roads and bitumen roofs [3,11]). In response to these limitations, many studies have already suggested and successfully proven the added benefits of fusing hyperspectral data with various other data, especially LiDAR data, for urban land cover mapping (e.g., [16,[56][57][58]).…”
Section: Urban Land Cover Mapping Using Hyperspectral Imagerymentioning
confidence: 68%
See 1 more Smart Citation
“…This information derived from remotely sensed datasets leads to an improved observation and monitoring that can benefit applied urban planning and management [2]. However, land cover mapping of the urban environment by means of the remote sensing remains a distinct challenge due to the strong diversity of materials and objects, leading to spectral heterogeneity and geometric complexity of the urban areas as well as the presence of the shadow scenes [3]. In fact, several studies have showed that current satellite data provide limited information to deal with the richness, heterogeneity and complexity of the materials and forms in the urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral sensors acquire nearly continuous spectral bands with hundreds of spectral channels to capture the diagnostic information of land-cover materials, opening new possibilities for remote sensing applications such as mineral exploration, precision agriculture, and disaster monitoring [1][2][3]. As an unsupervised information extraction technique, clustering is a very useful tool for hyperspectral image (HSI) interpretation.…”
Section: Introductionmentioning
confidence: 99%